Assessment of Geoeducation Program for Indigenous Students in Kenyir Geopark, Terengganu, Malaysia - Dony Adryansyah Nazaruddin; Norhayati Ab Manaf (Geoconservation Research)
Kenyir Geopark in Terengganu, Malaysia, was recognized as the country's ninth national geopark on May 30, 2023. Many stakeholders are now prepared to support conservation and development efforts in the geopark area. Universiti Malaysia Terengganu (UMT) as a local public university has taken some initiatives to develop local and indigenous communities in the geopark area through education programs focused on geoscience, called geoeducation, in collaboration with the Department of Mineral and Geoscience Malaysia (JMG) Terengganu and other agencies/institutions. The most recent Sungai Berua Geoschool Project (SBGP), is part of a series of geoeducation programs dedicated to indigenous communities, primarily for school kids living in the Sungai Berua village, Hulu Terengganu district, and coordinated under the Service Learning Malaysia University for Society (SULAM) initiative. This project provided an opportunity for UMT lecturers and students, as well as related partners, to teach basic geoscience and geopark knowledge to indigenous students through a variety of teaching modules including pre- and post-program questionnaires, presentations by facilitators, geoeducational games, coloring pictures of the geopark, and creating geoproducts. This study had three main objectives: first, to investigate the interest of all involved parties in geoscience and geopark topics; second, to examine teaching strategies and approaches to attract people to learn basic geoscience and geopark; and third, to analyze the project's benefits. This kind of project has the potential to be organized continuously to encourage the engagement of local or indigenous communities to improve their quality of education and economic level.